207k views
5 votes
Let f(x)=-3x and g(x) = 2x-1
Find the following: 4g(x) - f(x)

2 Answers

3 votes

Here, we are provided with two polynomials f(x) and g(x),and we need to find 4g(x) - f(x).

Given,

  • f(x) = -3x
  • g(x) = 2x - 1

Now,we need to find 4g(x) - f(x). We will simply substitute the given value of polynomials to get the answer.


4g(x) - f(x)


4(2x - 1) - ( - 3x)

Opening the parentheses,


8x - 4 + 3x

Now combing the like terms, and adding them,


8x + 3x - 4


\boxed{11x - 4}

This is our final result.

#CarryOnLearning

━━━━━━━━━━━━━━━━━━━━

User Felix Ebert
by
5.4k points
3 votes

Answer:

11x-4

Explanation:

f(x)=-3x

g(x) = 2x-1

4g(x) - f(x)

4(2x-1) - ( -3x)

Distribute

8x -4 +3x

Combine like terms

11x-4

User Bhantol
by
5.9k points